The Influence of Picture Story Books on Children's Language Development - Rizky Hafizotul Zikro; Izza Fitri; Tutut Handayani (EDUCATIO : Journal of Education, 2024)
This study investigates the impact of picture story books on the language development of children at KB Kasih Ibu in Tanjung Bulan Village, Rambang Kuang District, Ogan Ilir Regency. The research addresses the issue of children's listening skills not developing optimally due to monotonous activities and games. The objective is to determine whether picture story books influence children's listening abilities. This quantitative research utilizes a pre-experimental design, specifically the One-Group Pretest-Posttest model, involving a sample of 10 children. Data collection methods include observation, documentation, and tests, while data analysis involves validity, reliability, normality, homogeneity, and hypothesis testing. Results indicate that the average pretest and posttest scores were 23.50 and 33.00, respectively, with a significant difference (p < 0.05) between the two sets of scores. The findings confirm that picture story books significantly enhance children's language development at KB Kasih Ibu, supporting the hypothesis Ha.